Emerging issues in the further development of the resource-based view of the firm - Torsten Frohwein; Wolfgang Burr (Universität Stuttgart, Betriebswirtschaftliches Institut, Abteilung I - Forschungs-, Entwicklungs- und Innovationsmanagement, 2011)
The resource-based view is the dominant paradigm in strategic management. One of the unanswered questions is how innovations are addressed in the resource and competence based literature. In answering this question the conformance of the fundamental methodological principles of the resource-based reasoning with the defined explanation goals is challenged. Theoretical foundation based on transaction costs and property rights arguments can help to clarify a sufficient explanation of the emergence, occupation, and decay of sustainable competitive advantage. The necessity and the feasibility to integrate transaction costs and property rights aspects into the resource-based reasoning is to be proofed.
Keywords: 650; resource-based view; property rights; theory integration; innovations; strategic management